Citation Network Visualization of Reference Papers Based on Influence Groups - Choi, Gyeongcheol; Lim, Suhyun; Yoon, Taerin; Lee, Kyungwon (2018 IEEE 8th Symposium on Large Data Analysis and Visualization, LDAV 2018, 2018)
Survey of relevant research papers are very important in academic research to fully understanding the research trends in a given field of interest. Many researchers use keyword searches to investigate their related research. However, it is often difficult to find the desired research papers only through a keyword search. Here we propose a citation network visualization technique that constructs the genealogy of a research paper. It allows the user to trace the genealogy of the reference papers that form the basis of their research via large citation data sets, while also providing a visualization of how the research paper influences its research field.
Keywords: Academic research; Citation networks; Information visualization; Keyword search; Network visualization; Research fields; Research papers; Research trends; Citation Network; hierarchical Visualization; human-centered computing [Information visualization]; network Visualization